A roughening microetching solution with low adsorption amount of cuprous ions, a preparation method and applications thereof

CN121295183BActive Publication Date: 2026-10-27ZHUHAI BANMING TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511330885.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-17
Publication Date
2026-10-27
Estimated Expiration
2045-09-17

AI Technical Summary

Technical Problem

[0007]本发明的主要目的是提供一种亚铜离子低吸附量粗化微蚀液、制备方法及应用,旨在改善现有的微蚀液蚀刻后极易吸附亚铜离子,使粗化效果下降的技术问题

Benefits of technology

[0018]与现有技术相比,本发明的亚铜离子低吸附量粗化微蚀液具有以下有益效果:本发明提供的亚铜离子低吸附量粗化微蚀液包括含杂环结构的复合氧化剂、环己胺、有机酸、卤离子、铜离子、稳定剂,原料中的各组分协同作用,在基材板面形成一层保护膜,减少亚铜离子的吸附;同时在含杂环结构的复合氧化剂的作用下,使亚铜离子氧化成铜离子,减少后续酸洗步骤盐酸溶液中的铜离子含量,防止铜离子浓度太高,对粗化后的蜂窝状表面形貌再度蚀刻,影响粗化效果。此外,本发明提供的亚铜离子低吸附量粗化微蚀液体系中加入了稳定剂,组分不易分解,能长时间处于工作状态。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121295183B_ABST
    Figure CN121295183B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of etching solutions, in particular to a cuprous ion low-adsorption roughening micro-etching solution, a preparation method and application. The raw materials of the cuprous ion low-adsorption roughening micro-etching solution comprise a complex oxidizing agent containing a heterocyclic structure, cyclohexylamine, an organic acid, a halide ion source, a copper ion source, a stabilizer and water. The components in the raw materials synergistically form a protective film on the surface of a base plate, so that the adsorption of cuprous ions is reduced; meanwhile, the cuprous ions are oxidized into copper ions under the action of the complex oxidizing agent containing the heterocyclic structure, so that the copper ion content in hydrochloric acid solution in a subsequent pickling step is reduced, the copper ion concentration is prevented from being too high, the roughened honeycomb surface morphology is prevented from being etched again, and the roughening effect is affected. In addition, the cuprous ion low-adsorption roughening micro-etching solution system provided by the application is added with the stabilizer, the components are not prone to decomposition, and the system can be in a working state for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of etching solution technology, and in particular to a coarsening micro-etching solution with low adsorption of cuprous ions, its preparation method, and its application. Background Technology

[0002] Improving the adhesion between conductor copper and dielectric materials is a key process for increasing yield in the manufacturing of printed circuit boards, IC substrates, and copper-containing semiconductor wafers. Common methods to improve the adhesion between copper and dielectric polymers include mechanical brushing, sandblasting, volcanic ash, and chemical micro-etching roughening.

[0003] Chemical micro-etching is the most widely used method. Chemical micro-etching roughens the copper surface by chemically etching, increasing the contact area between copper and the dielectric polymer, thereby improving the anchoring force between them. Depending on the composition, the roughening micro-etching solution is divided into sulfuric acid-hydrogen peroxide system and organic acid-copper chloride system. The principle of copper surface roughening is based on copper etching, which follows the chemical reaction equations: Copper etching: Cu + CuCl2 → 2CuCl, CuCl + 2Cl - →[CuCl3] 2- Oxidation of air during spraying: 2CuCl + 2HCl + [O] → 2CuCl2 + H2O, Overall reaction: Cu + 2HCl + [O] = CuCl2 + H2O.

[0004] If a suitable pitting corrosion promoter is used in this process, specific adsorption can be formed on the Cu surface, resulting in numerous pitting corrosion points and a roughened, honeycomb-like morphology. Pitting corrosion occurs in two stages: nucleation and propagation. In the solution containing Cl... - When present, the passivation film on the metal surface has local defects, preventing further passivation. The potentials of the defective and undefective areas are inconsistent; the defective portion becomes the activated anode, and the surrounding area becomes the cathode, forming a closed cell. Due to the very small anode area and high current density, pitting nuclei form on the metal surface. After the pitting nuclei form, the dissolved metal ions undergo hydrolysis to generate H₂. + This causes a decrease in the pH of the local solution, which in turn accelerates the dissolution of the metal, further enlarging and deepening the pits. As the pits deepen, the migration of corroded material becomes more difficult, leading to a further decrease in the pH within the pits. Simultaneously, Cl... - Accumulation within the corrosion pits accelerates their expansion and deepening, eventually leading to pitting corrosion. The roughening mechanism of copper surface ultra-roughening solutions is based on the aforementioned theory of metal pitting corrosion. Pitting corrosion promoters primarily make it easier for defects or weak points on the copper surface (such as inclusions, grain boundaries, dislocations, etc.) to form pitting corrosion nuclei.

[0005] When copper foil is immersed in an acidic solution containing chloride ions, pitting corrosion will occur as long as the corrosion potential reaches or exceeds the pitting potential (or breakdown potential). Pitting corrosion is an autocatalytic process within the closed area. In a pit with a certain degree of occlusion, the concentration of dissolved copper ions increases. To maintain charge balance, chloride ions continuously migrate into the pit, leading to chloride ion enrichment. The high concentration of copper chloride hydrolyzes to produce hydrogen ions, creating a strongly acidic environment within the pit, which further accelerates the dissolution of copper, the increase in chloride ion concentration, and acidification. The inner wall of the pit is in an activated state (forming the anode of the corrosion galvanic cell), while the metal surface outside the pit remains in a passive state (forming the cathode). This forms a small anode / large cathode activation-passivation cell system, causing pitting corrosion to develop rapidly, forming pores. Numerous pitting points coarsen the copper surface, forming a honeycomb-like surface morphology.

[0006] After etching, the honeycomb-like surface morphology resulting from surface roughening readily adsorbs cuprous ions. In the subsequent acid pickling step, cuprous ions react with hydrogen ions in the hydrochloric acid solution to generate copper ions. The more cuprous ions adsorbed, the higher the copper ion concentration in the hydrochloric acid solution. When the copper ion concentration is too high, the copper ions begin to etch the already roughened copper surface under the action of HCl, thus reducing the roughening effect. During this period, there is also an imbalance between redox reactions: During etching, divalent copper ions (Cu...) 2+ The copper reacts with the copper to form cuprous chloride (CuCl), which adheres to the copper surface: Cu + Cu 2+ +2Cl→2CuCl. If the oxidant (such as H2O2, chlorate) is insufficient or ineffective, cuprous ions cannot be oxidized to Cu in time. 2+ This leads to Cu + 1. Continuous accumulation and adsorption at the etching interface. 2. Synergistic failure of corrosion inhibitors: Corrosion inhibitors can be added during etching, which inhibit excessive etching by adsorbing onto the copper surface. However, when the pH or temperature of the etching solution is unbalanced, the corrosion inhibitor may become deactivated, and cuprous ions and halide ions (Cl-) will react. - 3. Mass transfer kinetics barriers: When the viscosity of the high-concentration etching solution is too high or the spray pressure is insufficient, cuprous ions are difficult to peel off from the copper surface and diffuse into the bulk solution, resulting in local enrichment. Summary of the Invention

[0007] The main objective of this invention is to provide a coarsening micro-etching solution with low adsorption of cuprous ions, its preparation method, and its application, aiming to improve the technical problem that existing micro-etching solutions easily adsorb cuprous ions after etching, thus reducing the coarsening effect.

[0008] To achieve the above objectives, the present invention proposes a coarsening micro-etching solution with low adsorption capacity of cuprous ions. The raw materials of the coarsening micro-etching solution with low adsorption capacity of cuprous ions include: a composite oxidant containing a heterocyclic structure, cyclohexylamine, organic acid, halide ion source, copper ion source, stabilizer and water.

[0009] Preferably, the low adsorption capacity coarsening micro-etching solution for cuprous ions comprises, by mass concentration: 0.01~0.05 g / L of a composite oxidant containing a heterocyclic structure, 0.01~0.1 g / L of cyclohexylamine, 10~200 g / L of an organic acid, 1~100 g / L of halide ions from a halide ion source, 10~50 g / L of copper ions from a copper ion source, and 0.001~0.1 g / L of a stabilizer.

[0010] Preferably, the composite oxidant containing a heterocyclic structure is at least one of methyldioxane, dimethyldioxane, or a nitrocyclopropane derivative.

[0011] Preferably, the stabilizer is an amine-containing compound.

[0012] Preferably, the amine-containing compound includes at least one of methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, monoethanolamine, diethanolamine, or triethanolamine.

[0013] Preferably, the halide ion source includes one or two of sodium chloride, calcium chloride, potassium chloride, ammonium chloride, zinc chloride, or ferric chloride.

[0014] Preferably, the copper ion source includes at least one of copper sulfate, copper chloride, copper bromide, or copper formate tetrahydrate.

[0015] Preferably, the organic acid includes at least one selected from formic acid, acetic acid, malic acid, citric acid, tartaric acid, ethylenediaminetetraacetic acid, iminodisuccinic acid, monochloroacetic acid, dichloroacetic acid, trichloroacetic acid, glycine, serine, threonine, cysteine, or tyrosine.

[0016] In addition, the present invention also proposes a method for preparing the above-mentioned coarsening micro-etching solution with low adsorption capacity of cuprous ions, comprising the following preparation steps: S1. Weigh out copper ion source, organic acid and halide ion source according to mass concentration, add them to water in sequence and stir to dissolve to obtain the first solution; S2. Weigh out the composite oxidant containing the heterocyclic structure, cyclohexylamine, and stabilizer according to their mass concentration and dissolve them in the first solution to obtain the second solution; S3. Adjust the volume of the second solution to make the concentration of the heterocyclic composite oxidant and cyclohexylamine 0.0001~0.2g / L, to obtain the coarsening micro-etching solution with low adsorption of cuprous ions.

[0017] In addition, the present invention also proposes the application of the above-mentioned low adsorption amount of cuprous ions roughening micro-etching solution in the chemical micro-etching of copper foil surface.

[0018] Compared with existing technologies, the low-adsorption-capacity cuprous ion roughening micro-etching solution of the present invention has the following beneficial effects: The low-adsorption-capacity cuprous ion roughening micro-etching solution provided by the present invention comprises a composite oxidant containing a heterocyclic structure, cyclohexylamine, organic acid, halide ions, copper ions, and a stabilizer. The components in the raw materials work synergistically to form a protective film on the substrate surface, reducing the adsorption of cuprous ions. At the same time, under the action of the composite oxidant containing a heterocyclic structure, cuprous ions are oxidized into copper ions, reducing the copper ion content in the hydrochloric acid solution in the subsequent pickling step, preventing the copper ion concentration from being too high and re-etching the roughened honeycomb surface morphology, thus affecting the roughening effect. In addition, the low-adsorption-capacity cuprous ion roughening micro-etching solution system provided by the present invention contains a stabilizer, making the components less prone to decomposition and allowing them to remain in working condition for a long time. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 The image shows a scanning electron microscope (SEM) image of a copper circuit board after acid washing with the low-adsorption-amount roughening micro-etching solution for cuprous ions prepared in Example 1. Figure 2 The image shows a scanning electron microscope (SEM) image of a copper circuit board after acid etching with the roughening micro-etching solution prepared in Comparative Example 5. Figure 3 The image shows a scanning electron microscope (SEM) image of a copper circuit board after acid etching with the roughening micro-etching solution prepared in Comparative Example 6. Figure 4 The image shows a scanning electron microscope (SEM) image of a copper circuit board after being acid-etched with the roughening micro-etching solution prepared in Comparative Example 7.

[0021] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0023] Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.

[0024] A coarsening micro-etching solution with low adsorption capacity of cuprous ions, the raw materials of which include: a composite oxidant containing a heterocyclic structure, cyclohexylamine, organic acid, halide ion source, copper ion source, stabilizer and water.

[0025] This low-adsorption-capacity coarsening micro-etching solution effectively prevents the adsorption of cuprous ions and also has high stability, making it compatible with coarsening micro-etching of substrates of different materials.

[0026] In addition, an appropriate amount of pH buffer can be added to the coarsening micro-etching solution in this scheme according to production needs to obtain a coarsening micro-etching solution with low adsorption of cuprous ions at the required pH value.

[0027] Based on mass concentration, the low adsorption capacity of cuprous ions in the roughening micro-etching solution comprises: 0.01~0.05 g / L of a composite oxidant containing a heterocyclic structure, 0.01~0.1 g / L of cyclohexylamine, 10~200 g / L of an organic acid, 1~100 g / L of halide ions from a halide ion source, 10~50 g / L of copper ions from a copper ion source, and 0.001~0.1 g / L of a stabilizer.

[0028] The heterocyclic composite oxidant is at least one of methyldioxane (TFDO, molecular formula C3H3F3O2), dimethyldioxane (DDO, molecular formula C3H6O2), or a nitrocyclopropane derivative (usually with the molecular formula R1R2CONR3), where R is a group with any number of carbon atoms. Using two or more of the above heterocyclic oxidants results in a better composite effect, with a preferred concentration of 0.03 g / L.

[0029] The stabilizer is an amine-containing compound; the amine-containing compound includes at least one of methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, monoethanolamine, diethanolamine, or triethanolamine; the halide ion source includes one or two of sodium chloride, calcium chloride, potassium chloride, ammonium chloride, zinc chloride, or ferric chloride; the copper ion source includes at least one of copper sulfate, copper chloride, copper bromide, or copper formate tetrahydrate; the organic acid includes at least one of formic acid, acetic acid, malic acid, citric acid, tartaric acid, ethylenediaminetetraacetic acid, iminodisuccinic acid, monochloroacetic acid, dichloroacetic acid, trichloroacetic acid, glycine, serine, threonine, cysteine, or tyrosine.

[0030] This invention also proposes a method for preparing the above-mentioned low-adsorption-capacity coarsening micro-etching solution of cuprous ions, comprising the following preparation steps: S1. Weigh out copper ion source, organic acid and halide ion source according to mass concentration, and add them to (deionized) water in sequence and stir to dissolve to obtain the first solution; S2. Weigh out the heterocyclic composite oxidant, cyclohexylamine and stabilizer according to mass concentration and dissolve them in the first solution to obtain the second solution (the heterocyclic composite oxidant needs to be added in this step to avoid inactivation). S3. Adjust the volume of the second solution to make the concentration of the heterocyclic composite oxidant and cyclohexylamine 0.0001~0.2g / L, to obtain the coarsening micro-etching solution with low adsorption of cuprous ions.

[0031] Traditional organic acid-based roughening micro-etching solutions activate the copper surface, creating an environment conducive to pitting corrosion. This accelerates pitting corrosion on the copper surface, resulting in a honeycomb structure and ultimately a rough surface morphology. The rough surface morphology is beneficial for Cu... + Adsorption.

[0032] The coarsening micro-etching solution with low cuprous ion adsorption in this scheme comprises organic acid, halide ion source, copper ion source, stabilizer, heterocyclic composite oxidant, and cyclohexylamine. Through the synergistic effect of these multiple components, efficient etching and cuprous ion control are achieved. The heterocyclic composite oxidant can balance the chemical potential of different copper layers and can also directly adsorb and oxidize CuCl, thus reducing Cu... + Cu oxide 2+ This allows it to dissolve in water, reducing the amount of Cu entering the subsequent pickling process. 2+ Quantity; Cyclohexylamine complexes with the copper surface via electron coordination, reducing Cu content. + The adsorption of organic acid-halogen ions creates an acidic etching environment, which, together with the copper ion source, regulates the etching rate. The stabilizer can maintain the dispersion stability of the solution components and prevent component decomposition.

[0033] The structure of cyclohexylamine is shown in general chemical formula (Ⅰ): General chemical formula (Ⅰ).

[0034] Furthermore, the preferred concentration of the organic acid is 20 g / L to 180 g / L; the preferred concentration of the halide ion is 15 g / L to 85 g / L.

[0035] The present invention also proposes the application of the above-mentioned low adsorption amount of cuprous ions roughening micro-etching solution in the chemical micro-etching of copper foil surface.

[0036] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.

[0037] Example 1 A method for preparing a roughening micro-etching solution with low adsorption capacity of cuprous ions includes the following preparation steps: S1. Weigh out 75g of copper ion source (copper sulfate), 80g of organic acid (acetic acid) and 72g of halide ion source (sodium chloride) according to mass concentration, and add them to water in sequence and stir to dissolve to obtain the first solution; S2. Weigh 0.03 g of the heterocyclic composite oxidant (methyldioxane), 0.03 g of cyclohexylamine, and 0.05 g of the stabilizer (diethanolamine) according to their mass concentrations and dissolve them in the first solution to obtain the second solution; S3. The second solution is brought to a final volume of 1L, so that the concentration of the heterocyclic composite oxidant and cyclohexylamine is 0.03g / L, thus obtaining the low-adsorption-capacity coarsening micro-etching solution for cuprous ions.

[0038] Example 2 A method for preparing a roughening micro-etching solution with low adsorption capacity of cuprous ions includes the following preparation steps: S1. Weigh 25g of copper ion source (such as copper sulfate), 20g of organic acid (acetic acid) and 24g of halide ion source (sodium chloride) according to mass concentration, add them to water in sequence and stir to dissolve to obtain the first solution; S2. Weigh 0.01 g of the heterocyclic composite oxidant (methyldioxane), 0.01 g of cyclohexylamine, and 0.001 g of the stabilizer (diethanolamine) according to their mass concentrations and dissolve them in the first solution to obtain the second solution; S3. The second solution is brought to a final volume of 1L, so that the concentration of the heterocyclic composite oxidant is 0.01g / L and the concentration of cyclohexylamine is 0.01g / L, thus obtaining the coarsening micro-etching solution with low adsorption capacity of cuprous ions.

[0039] Example 3 A method for preparing a roughening micro-etching solution with low adsorption capacity of cuprous ions includes the following preparation steps: S1. Weigh out 125g of copper ion source (copper sulfate), 180g of organic acid (acetic acid) and 136g of halide ion source (sodium chloride) according to mass concentration, and add them to water in sequence and stir to dissolve to obtain the first solution; S2. Weigh 0.05 g of the heterocyclic composite oxidant (dimethyldioxane), 0.1 g of cyclohexylamine, and 0.1 g of the stabilizer (ethylamine) according to their mass concentrations and dissolve them in the first solution to obtain the second solution; S3. Adjust the volume of the second solution so that the concentration of the heterocyclic composite oxidant is 0.05 g / L and the concentration of cyclohexylamine is 0.1 g / L, to obtain the cuprous ion low adsorption capacity roughening micro-etching solution.

[0040] Comparative Example 1 In this comparative example, all preparation steps and parameters are the same as in Example 1, except that: Pick Use a conventional oxidant—hydrogen peroxide.

[0041] Comparative Example 2 In this comparative example, all preparation steps and parameters are the same as in Example 1, except that: Pick Use other oxidizing agents—3-aminopyridine.

[0042] Comparative Example 3 This comparative example uses an existing acidic roughening micro-etching solution, which consists of copper chloride, formic acid, and sodium chloride. The concentration of copper chloride (based on copper ions) is 20 g / L, formic acid is 30 g / L, sodium chloride is 40 g / L, and the remainder is water.

[0043] Comparative Example 4 This comparative example uses an existing acidic roughening micro-etching solution, whose components are copper chloride, formic acid, sodium chloride, and diethylamine. Based on copper ions, the concentration of copper chloride is 20 g / L, formic acid is 30 g / L, sodium chloride is 40 g / L, diethylamine is 0.02 g / L, and the remainder is water.

[0044] Comparative Example 5 In this comparative example, all preparation steps and parameters are the same as in Example 1, except that no composite oxidant containing heterocyclic structures and cyclohexylamine are added.

[0045] Comparative Example 6 In this comparative example, all preparation steps and parameters are the same as in Example 1, except that no composite oxidant containing a heterocyclic structure is added.

[0046] Comparative Example 7 In this comparative example, all preparation steps and parameters are the same as in Example 1, except that cyclohexylamine was not added.

[0047] The copper ion low-adsorption roughening micro-etching solutions prepared in Examples 1-3 and the roughening micro-etching solutions prepared in Comparative Examples 1-7 were subjected to the following performance tests: Copper circuit boards were subjected to roughening micro-etching treatment. During the roughening treatment, the method of contacting the roughening micro-etching solution with the copper surface was spraying (specifically, spraying was performed at a micro-etching agent temperature of 25°C for 60 seconds). After the roughening treatment, the substrate was rinsed with an acidic aqueous solution (5wt% hydrochloric acid solution), followed by rinsing with deionized water, and finally dried.

[0048] The specific test results are shown in the table below:

[0049] Note: Cuprous ions are oxidized to copper ions in an acidic environment. Furthermore, the PCB board / copper circuit board in this solution undergoes a DI water wash before being pickled in hydrochloric acid solution to remove copper ions adhering to the surface. The pickling solution is a 5% hydrochloric acid solution, which under normal circumstances does not react with the copper on the PCB board surface. Therefore, the copper ion concentration in the hydrochloric acid solution detected in this solution can essentially represent the amount of cuprous ions adsorbed.

[0050] The test results from Examples 1-3 above show that the low adsorption capacity of cuprous ions in this method for roughening micro-etching solution has a good effect on the Cu content of copper surfaces. 2+ Adsorption capacity (i.e., Cu) + The adsorption capacity can be reduced to 20 ppm, the surface roughness of the copper circuit board can be maintained in the range of 0.5~0.65 μm, and the roughening micro-etching solution remains effective after long-term storage, with the longest effective period extended to 60 days.

[0051] The test results of Example 1 and Comparative Examples 1-2 show that after replacing the composite oxidant with a heterocyclic structure in this scheme with other types of oxidants, the surface roughening performance and the ability to reduce cuprous ion adsorption of the prepared roughened micro-etching solution are significantly reduced.

[0052] The test results of Examples 1-3 and Comparative Examples 3-4 show that, compared with the existing acidic roughening micro-etching solutions, the cuprous ion low adsorption roughening micro-etching solution of this scheme has better surface roughening performance and reduced cuprous ion adsorption performance.

[0053] The test results of Example 1 and Comparative Examples 5-7 show that when no composite oxidant containing heterocyclic structure or cyclohexylamine is added, the surface roughening performance and the ability to reduce cuprous ion adsorption of the prepared roughened micro-etching solution decrease.

[0054] Example 4 In this embodiment, all preparation steps and parameters are the same as in Example 1, except that the type of composite oxidant containing a heterocyclic structure used is different, as shown in the table below:

[0055] The cuprous ion low adsorption capacity roughening micro-etching solution prepared in Example 4 above was subjected to the following performance tests, and the specific test results are shown in the table below:

[0056] As shown in the test results of Example 4 above, the composite oxidant containing heterocyclic structures in the low adsorption capacity coarsening micro-etching solution of cuprous ions in this scheme is preferably used in combination with two types. Among them, the combination of methyldioxane and 1-oxazolidinyl propane-2-carboxylic acid ester has better effect, and the preferred concentration ratio of the two is 1:1. 2+ Adsorption capacity (i.e., Cu) + The adsorption capacity can be reduced to 18 ppm, the surface roughness of the copper circuit board can be maintained at 0.65~0.67 μm, and the roughening micro-etching solution remains effective after long-term storage, with the longest shelf life extended to 60 days.

[0057] Furthermore, the combination of the three heterocyclic composite oxidants specified in this scheme also shows good results for the Cu on the copper surface. 2+ Adsorption capacity (i.e., Cu) + The adsorption capacity can be reduced to 15 ppm.

[0058] Example 5 A method for preparing a roughening micro-etching solution with low adsorption capacity of cuprous ions includes the following preparation steps: S1. Weigh out 75g of copper ion source (copper sulfate), 120g of organic acid (formic acid) and 60g of halide ion source (sodium chloride) according to mass concentration, and add them to water in sequence and stir to dissolve to obtain the first solution; S2. Weigh 0.03g of the composite oxidant containing heterocyclic structure (methyldioxane and 1-oxazolidinyl propane-2-carboxylic acid ester, 15mg each), 0.3g of cyclohexylamine, and 0.3g of stabilizer (dihexylamine) according to mass concentration and dissolve them in the first solution to obtain the second solution; S3. The second solution is brought to a final volume of 1L, so that the concentration of the heterocyclic composite oxidant and cyclohexylamine is 0.03g / L, thus obtaining the low-adsorption-capacity coarsening micro-etching solution for cuprous ions.

[0059] The cuprous ion low adsorption capacity roughening micro-etching solution prepared in Example 5 above was subjected to the following performance tests, and the specific test results are shown in the table below:

[0060] By systematically optimizing the ratio of methyldioxane to 1-oxazolidinyl propane-2-carboxylic acid ester in the composite oxidant, and precisely controlling the addition amounts of cyclohexylamine and dihexylamine, the stability and etching efficiency of the micro-etching solution can be significantly improved. In practical applications, this micro-etching solution is suitable for roughening high-density interconnect substrates, effectively reducing the risk of cuprous ion residue, ensuring a surface uniformity of 0.65~0.68μm after etching, and maintaining a shelf life of 60 days, making it suitable for large-scale production environments. Furthermore, by adjusting the component concentration according to the characteristics of different substrate materials, its application potential in fields such as flexible circuit boards can be expanded.

[0061] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

Claims

1. A coarsening micro-etching solution with low adsorption capacity of cuprous ions, characterized in that, The raw materials of the low adsorption capacity of cuprous ions roughening micro-etching solution include: a composite oxidant containing a heterocyclic structure, cyclohexylamine, organic acid, halide ion source, copper ion source, stabilizer and water; Based on mass concentration, the low adsorption capacity of cuprous ions in the roughening micro-etching solution comprises: 0.01~0.05 g / L of a composite oxidant containing a heterocyclic structure, 0.01~0.1 g / L of cyclohexylamine, 10~200 g / L of organic acid, 1~100 g / L of halide ions from a halide ion source, 10~50 g / L of copper ions from a copper ion source, and 0.001~0.1 g / L of stabilizer; The heterocyclic composite oxidant is a combination of methyldioxane and 1-oxazolidinyl propane-2-carboxylic acid ester, or a combination of methyldioxane and dimethyldioxane, or a combination of dimethyldioxane and 1-oxazolidinyl propane-2-carboxylic acid ester, or a combination of methyldioxane, dimethyldioxane, and 1-oxazolidinyl propane-2-carboxylic acid ester. This heterocyclic composite oxidant is used to directly adsorb and oxidize CuCl, reducing CuCl... + Oxidized to Cu 2+ The cyclohexylamine is used to reduce Cu by electron coordination complexation on the copper surface. + Adsorption.

2. The cuprous ion low-adsorption coarsening micro-etching solution according to claim 1, characterized in that, The stabilizer is an amine-containing compound.

3. The cuprous ion low-adsorption coarsening micro-etching solution according to claim 2, characterized in that, The amine-containing compound includes at least one of methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, monoethanolamine, diethanolamine, or triethanolamine.

4. The cuprous ion low-adsorption coarsening micro-etching solution according to claim 1, characterized in that, The halide ion source includes one or two of sodium chloride, calcium chloride, potassium chloride, ammonium chloride, zinc chloride, or ferric chloride.

5. The cuprous ion low-adsorption coarsening micro-etching solution according to claim 1, characterized in that, The copper ion source includes at least one of copper sulfate, copper chloride, copper bromide, or copper formate tetrahydrate.

6. The cuprous ion low-adsorption coarsening micro-etching solution according to claim 1, characterized in that, The organic acid includes at least one of formic acid, acetic acid, malic acid, citric acid, tartaric acid, ethylenediaminetetraacetic acid, iminodisuccinic acid, monochloroacetic acid, dichloroacetic acid, trichloroacetic acid, glycine, serine, threonine, cysteine, or tyrosine.

7. A method for preparing a low-adsorption-capacity coarsening micro-etching solution for cuprous ions as described in any one of claims 1-6, characterized in that, The preparation steps include the following: S1. Weigh out copper ion source, organic acid and halide ion source according to mass concentration, add them to water in sequence and stir to dissolve to obtain the first solution; S2. Weigh out the composite oxidant containing the heterocyclic structure, cyclohexylamine, and stabilizer according to their mass concentration and dissolve them in the first solution to obtain the second solution; S3. Adjust the volume of the second solution to make the concentration of the composite oxidant containing the heterocyclic structure and cyclohexylamine 0.0001~0.2g / L, to obtain the coarsening micro-etching solution with low adsorption of cuprous ions.

8. The application of a low-adsorption-capacity coarsening micro-etching solution for cuprous ions as described in any one of claims 1-6 in the chemical micro-etching of copper foil surfaces.

Citation Information

Patent Citations

  • Novel PCB copper reduction etching liquid and manufacturing technology

    CN109652804A

  • Alkaline micro-etching liquid for roughening copper surface

    CN116815187A

  • Medical solution used for etching processing

    JP2022181453A